VARIETIES OF SOCIAL DISCIPLINING, HISTORICAL PERSPECTIVES. - Mantecón Movellán, Tomás A. (Revista de Historia Social y de las Mentalidades, 2011)
Historical thought has tended to explain social disciplining according to two main analytical perspectives: on one hand, German tradition about the so-called sozialdisziplinierung and, on the other hand, Foucault perspectives (focussed on disciplines practiced on the bodies-and/or-minds of people by the authorities). From these both viewpoints social disciplining was a dynamic ingredient of change, from traditional societies up to contemporary liberal societies; a machinery to provoke top-down changes (from above). On the bases of historical evidences, this research claims for a third viewpoint that stresses dynamics of social discipline and social disciplining from below; underlines the need of integrating this third perspective in the historical explanation of change in past societies throughout the analysis of social practices of everyday life; the values underneath them and, in the end, taking into account varieties of discipline and perspectives of social disciplining from below.